TENDENCIES OF REFORMING THE PEDAGOGICAL EDUCATION SYSTEM OF SWEDEN AT THE TURN OF XX - XXI CENTURIES - Kosharna, Natalia (Educological discourse, 2019)
The article is devoted to the question of the effectiveness of reforming the system of pedagogical education of Sweden at the turn of the XX - XXI centuries. The tendencies of changes in the system of pedagogical education of Sweden that were determined by historical traditions, the specifics of the organization of pedagogical education in the country, the fundamental material and technical basis, the level of professional competence of teachers, the differentiation of the educational process, the cooperation of teachers, teachers of partner schools and students during study and research work. While preserving the achievements in the foundation of school and vocational education, the Swedish pedagogical system of education has reoriented the educational process to form students and students the desire and ability to independently acquire knowledge from various sources of information in order to further utilize the acquired knowledge in life and further professional activities.